CT Angiographic Study of Anatomical Variations of Aortic Arch Branches in Libyan Patients - Elomami, Ibrahim M. M.; Karwad, Mustafa A; Nouh, Fatimah A; Haidar, Murshed H.; Hawla, Hawa M. R.; Elsherif, Alsanussi Tahir; Elzaidi, Narges M. (Scientific Journal of University of Benghazi, 2021)
The aim of this study is to determine the prevalence of the aortic arch branches variations in Libyan patients. The proportion of each type will be determined. Subjects and methods: This retrospective study was carried out on 229 cancer patients referred to the CT Scan Department for enhanced chest CT scanning. The scans showed that 83% of the patients had classical aortic arch branching patterns, and 17% had aortic arch variations. Bovine arch variation was the most common variation seen, reaching 11.4%, in which brachiocephalic and left common carotid arteries arise from the aortic arch in a common trunk. The prevalence of the left vertebral artery type that originates from the aortic arch was 3.9%. The prevalence of the aberrant right subclavian artery type was 2.6%, and of the aberrant right subclavian artery with common carotid trunk type was 1.74%. No relationship was found between gender and aortic arch branches variations. We conclude that aortic arch branching variations exist and hence, attention must be paid during chest surgical operations/radiological interventions to ensure safe procedure outcomes. Also, a CT scan is a good method to study such variations and the associated branching patterns.